2022
DOI: 10.3389/fimmu.2022.929040
|View full text |Cite
|
Sign up to set email alerts
|

Using a Relative Quantitative Proteomic Method to Identify Differentially Abundant Proteins in Brucella melitensis Biovar 3 and Brucella melitensis M5-90

Abstract: Brucellosis, caused by Brucella spp., is one of the most widespread bacterial zoonoses worldwide. Vaccination is still considered the best way to control brucellosis. An investigation into the differential proteome expression patterns of wild and vaccine strains may help researchers and clinicians differentiate between the strains to diagnose and better understand the mechanism(s) underlying differences in virulence. In the present study, a mass spectrometry-based, label-free relative quantitative proteomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Many studies have suggested several vaccine candidates for DIVA vaccines such as VjbR and BtpA proteins contributed to the virulence of the Y3 and M5 Brucella strains. Zur protein, ABC transporters, and thiamine metabolism-associated proteins may play crucial roles in Brucella survival and pathogenesis ( 148 ). In parallel, Uslu and Erganis revealed that B. melitensis Rev.1 ΔOmp19 can act as a DIVA marker vaccine using an ELISA test for the detection of the Omp19 protein ( 149 ).…”
Section: Immunitymentioning
confidence: 99%
“…Many studies have suggested several vaccine candidates for DIVA vaccines such as VjbR and BtpA proteins contributed to the virulence of the Y3 and M5 Brucella strains. Zur protein, ABC transporters, and thiamine metabolism-associated proteins may play crucial roles in Brucella survival and pathogenesis ( 148 ). In parallel, Uslu and Erganis revealed that B. melitensis Rev.1 ΔOmp19 can act as a DIVA marker vaccine using an ELISA test for the detection of the Omp19 protein ( 149 ).…”
Section: Immunitymentioning
confidence: 99%
“…Y3 ( B. melitensis biovar 3) is one of the most common pathogens of brucella, causing 80% of the global epidemic of brucellosis. 15 A19 ( Brucella abortus strains A19) is a vaccine used to prevent brucellosis in about 70% of countries 16 (Scheme 1A). Therefore, we analyzed and compared the complete genome sequences of A19 and Y3, 17 which were obtained from the official website of NCBI.…”
Section: Introductionmentioning
confidence: 99%